2015
DOI: 10.1002/2014jd022458
|View full text |Cite
|
Sign up to set email alerts
|

The effects of leaf size and microroughness on the branch‐scale collection efficiency of ultrafine particles

Abstract: Key Points:• UFP collection efficiency ( ) for four broadleaf species was measured• Rougher surfaces enhance ϵ even for hydraulically smooth flow • Longer leaf dimension has a thicker quasi-laminar boundary layer and smaller ϵ Abstract Wind tunnel experiments were performed to explore how leaf size and leaf microroughness impact the collection efficiency of ultrafine particles (UFP) at the branch scale. A porous media model previously used to characterize UFP deposition onto conifers (Pinus taeda and Juniperus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 63 publications
(125 reference statements)
1
9
0
Order By: Relevance
“…Wedding et al [1975] reported increases by a factor of 10 in deposition rates for particles to pubescent leaves compared to smooth, waxy leaves. This was confirmed by further wind tunnel studies reported by Wedding et al [1977] and in recent work by Huang et al [2015].…”
Section: Deposition Processessupporting
confidence: 87%
“…Wedding et al [1975] reported increases by a factor of 10 in deposition rates for particles to pubescent leaves compared to smooth, waxy leaves. This was confirmed by further wind tunnel studies reported by Wedding et al [1977] and in recent work by Huang et al [2015].…”
Section: Deposition Processessupporting
confidence: 87%
“…Approaches to describe aerosol deposition fluxes include big-leaf schemes in climate models, rough boundary layers used in air quality models, and multilayered models used in ecosystem studies (Feng 2008;Huang et al 2014Huang et al , 2015Katul et al 2010;Peters and Eiden 1992;Petroff et al 2008;Wesely and Hicks 2000). Deposition models require a general understanding of the processes involved, and credible results can be achieved when relevant environmental factors are sufficiently known.…”
Section: Quantification Of Deposited Aerosolsmentioning
confidence: 99%
“…Deposition may be enhanced by residual turbulent fluctuations very near the deposition surface ("near-wall" effects, Botto et al 2005;Guha 2008;Marchioli et al 2006;Parker et al 2008). These effects are poorly characterized and require further consideration to reconcile theory with the results of wind tunnel experiments and environmental loading of fine aerosol to leaves (Burkhardt et al 1995;Freer-Smith et al 2004;Huang et al 2015;Wiman 1986). …”
mentioning
confidence: 93%
“…This finding is supported by results from similar studies, which also found that coniferous (needleleaf) species generally offer higher deposition velocities than broadleaf species 36,37,102,105,106 . Saebø et al 36 suggest that the long and narrow shape of needle leaves offer a thinner quasi-laminar boundary layer than that of broadleaves, which offers comparatively less resistance to deposition via a shortened diffusional path length 107 . Chen et al 105 concur that many conifers are generally more effective for PM accumulation and post-rainfall re-capture due to their acicular, needlelike shape.…”
Section: Density and Porositymentioning
confidence: 99%
“…However, Leonard et al 78 found that leaf shape does influence PM deposition, albeit to a lesser extent than leaf surface characteristics. Indeed, a number of studies have found that complex leaf shapes are generally more effective than simple leaf shapes 78,[89][90][91]107 . In an evaluation of leaf traits for PM deposition, Weerakkody et al 91 erected experimental rigs containing both synthetic and natural leaves alongside a busy road, including synthetic leaves of different shapes but with identical surface areas and surface characteristics.…”
Section: Density and Porositymentioning
confidence: 99%